The Effect of Right Issue on The Stock Performance of PT Bank Syariah Indonesia Tbk (BRIS): Pengaruh Right Issue Terhadap Kinerja Saham PT Bank Syariah Indonesia Tbk (BRIS) - Rukmini, Mimin; Izzani Ulfi; Riskayanto (Universitas Muhammadiyah Sidoarjo, 2024)
The right issue policy is carried out by companies that have gone public. It usually aims to expand its business by increasing the capital obtained from old investors through Pre-emptive Rights. This study aims to test and find out how the difference in stock performance at PT Bank Syariah Indonesia Tbk (BRIS) before and after the right issue corporate action. This study uses secondary data sourced from various existing writings and publications such as those used in this study, namely retrieval of historical stock price data through the official website bankbsi.co.id owned by Bank Syariah Indonesia, and historical data on the Jakarta Composite Index (JCI) through the investing.com page. The sampling method used in this study was purposive sampling. Samples in this study were taken from stock prices for 5 (five) months before and after the right issue event in December 2022. The results of this study indicate that the right issue has no significant effect on stock performance when viewed from stock returns. However, the right issue has a significant influence when viewed from the abnormal stock return. Suggestions for further research can increase the observation time of the right issue event and the use of different abnormal stock return analysis models such as the market model or market adjusted model.